High-wear-resistance modified polypropylene material and preparation process thereof

By using random copolymerized polypropylene and other modified materials, combined with specific preparation processes, the problem of insufficient performance of traditional polypropylene materials in low temperature and high wear situations is solved, and the cold resistance, low temperature impact and wear resistance of highly wear-resistant modified polypropylene materials are significantly improved.

CN119823500AInactive Publication Date: 2025-04-15GRANDCHESS DAOAN CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510320300.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The application of traditional polypropylene materials in low-temperature environments and high-wear occasions is limited, with poor cold resistance and low-temperature impact, and insufficient wear resistance and material compatibility.

Method used

Random copolymerized polypropylene is used as the basic resin, combining low-density polyethylene, nano-scale silicon carbide, bronze powder and polyurethane elastomer and other materials, and through a specific preparation process, a highly wear-resistant modified polypropylene material is formed.

Benefits of technology

It significantly improves the toughness and low-temperature performance of the material, enhances cold resistance, low-temperature impact, wear resistance and material compatibility, and is suitable for various application scenarios that require high wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823500A_ABST
    Figure CN119823500A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of macromolecules, and discloses a high wear-resistant modified polypropylene material and a preparation process thereof, the material comprises the following raw materials by weight: 40-50 parts of polypropylene random copolymer, 10-20 parts of a flexibilizer, 10-20 parts of an elastomer, 10-20 parts of a wear-resistant filler, 10-20 parts of a reinforcing agent, 10-20 parts of a compatilizer, 10-20 parts of a surface slipping agent and 10-20 parts of an auxiliary agent. 10 to 14 parts of low density polyethylene; 6-10 parts of ethylene propylene diene monomer; 7-9 parts of nanoscale silicon carbide; 10 to 13 parts of an ethylene-octylene polymer; 5-8 parts of a polyurethane elastomer; 1.3 to 1.8 parts of bronze powder; 4-5 parts of nanoscale zinc oxide; 2-4 parts of an antioxidant; 0.8 to 1.1 parts of oleamide; according to the present invention, the polypropylene random copolymer is adopted to replace the conventional polypropylene, the low density polyethylene according to the formula ratio is added as the base resin, the bronze powder and the nano-scale material are adopted as the filling material and the auxiliary agent, and the set preparation process is combined, such that the cold resistance and the low temperature impact resistance of the final finished product material are increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymers, in particular to a highly wear-resistant modified polypropylene material and a preparation process thereof. Background Art

[0002] In the traditional raw material formula and preparation process, although polypropylene (PP) material has the advantages of low density and good processing performance, its cold resistance and low-temperature impact resistance are poor, and its wear resistance and material compatibility are insufficient. These defects limit its application in low-temperature environments and high-wear occasions. In order to overcome these shortcomings, researchers have introduced toughening agents, inorganic fillers, and used special lubricants to modify the material to improve its toughness and wear resistance.

[0003] However, these methods often fail to balance the high wear resistance and good low-temperature impact resistance of the material. For example, although adding molybdenum disulfide and epoxy resin can significantly improve the wear resistance, it may have an adverse effect on the toughness of the material. In addition, although the traditional copolymerization and blending modification methods can improve the impact resistance of the material, it still suffers from embrittlement in low-temperature environments.

[0004] Therefore, it is particularly important to develop a polypropylene composite material that can maintain high wear resistance and excellent low-temperature impact resistance. This new material not only needs to improve its cold resistance without sacrificing wear resistance, but also needs to ensure the mechanical strength and service life of the material under complex working conditions. Summary of the invention

[0005] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a highly wear-resistant modified polypropylene material and a preparation process, which has the advantages of cold resistance and low-temperature impact resistance, high wear resistance and strong material compatibility, and solves the problems of poor cold resistance and low-temperature impact resistance, and insufficient wear resistance and material compatibility of traditional materials.

[0006] (II) Technical solution To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a highly wear-resistant modified polypropylene material, which is composed of a base resin, a toughening agent, an elastomer, a wear-resistant filler, a reinforcing agent, a compatibilizer, a surface lubricant and an additive. The raw materials and their weight parts include: 40-50 parts of random copolymer polypropylene; 10-14 parts of low-density polyethylene; 6-10 parts of ethylene propylene rubber; 7-9 parts of nano-scale silicon carbide; 10-13 parts of ethylene-octene polymer; 5-8 parts of polyurethane elastomer; 1.3-1.8 parts of bronze powder; 4-5 parts of nano-scale zinc oxide; 2-4 parts of antioxidant; 0.8-1.1 parts of oleic acid amide; and 1.5-3 parts of silicone masterbatch.

[0007] Preferably, the base resin is composed of random copolymer polypropylene and low-density polyethylene, the toughening agent is composed of EPDM rubber and ethylene-octene polymer, the elastomer is composed of polyurethane elastomer, the wear-resistant filler is composed of nano-scale silicon carbide and bronze powder, the reinforcing agent is composed of nano-scale zinc oxide, the compatibilizer is composed of silicone masterbatch, the surface lubricant is composed of oleic acid amide, and the auxiliary agent is composed of an antioxidant.

[0008] Preferably, the raw materials and their weight parts include: 45 parts of random copolymer polypropylene; 13 parts of low-density polyethylene; 9 parts of EPDM rubber; 9 parts of nano-silicon carbide; 11 parts of ethylene-octene polymer; 6 parts of polyurethane elastomer; 1.35 parts of bronze powder; 4.2 parts of nano-zinc oxide; 2.2 parts of antioxidant; 0.98 parts of oleic acid amide; and 1.8 parts of silicone masterbatch.

[0009] Preferably, the raw materials and their weight parts include: 50 parts of random copolymer polypropylene; 11 parts of low-density polyethylene; 7 parts of EPDM rubber; 7 parts of nano-silicon carbide; 13 parts of ethylene-octene polymer; 5 parts of polyurethane elastomer; 1.7 parts of bronze powder; 4.4 parts of nano-zinc oxide; 2.6 parts of antioxidant; 0.91 parts of oleic acid amide; and 2.4 parts of silicone masterbatch.

[0010] Preferably, the preparation process of the random copolymer polypropylene is: S1.1. Prepare raw materials: prepare ethylene and propylene in a molar ratio of 0.01-0.04 and add them into the reactor; S1.2, control the reactor conditions: control the reactor temperature between 60-80°C, and the reactor pressure between 2-4MPa; S1.3, polymerization reaction: adding 2% metallocene catalyst based on the total mass of ethylene and propylene into the reactor, controlling the reaction time to be between 15 and 30 minutes, and obtaining a reactant; S1.4. Separation and purification: After the polymerization reaction is completed, the reactants are separated and purified to remove unreacted monomers and other impurities, and finally random copolymer polypropylene is obtained.

[0011] Preferably, the microhardness of the nano-scale silicon carbide is 2840-3320 kg / mm², which is between corundum and diamond, and the mechanical strength is higher than that of corundum. The particle size of the nano-scale zinc oxide is 30-100 nm, the average particle size is 50 nm, and the specific surface area is greater than 4 m² / g.

[0012] Preferably, a preparation process of a highly wear-resistant modified polypropylene material is prepared according to the raw materials and weight portions of the above-mentioned highly wear-resistant modified polypropylene material, and the preparation process is as follows: Step 1, raw material preparation: prepare random copolymer polypropylene, low-density polyethylene, EPDM rubber, nano-silicon carbide, ethylene-octene polymer, polyurethane elastomer, bronze powder, nano-zinc oxide, antioxidant, oleic acid amide and silicone masterbatch in parts by weight of the formula; Step 2, pretreatment: subject nano-sized silicon carbide and nano-sized zinc oxide to ultrasonic dispersion treatment for 20-30 minutes, and preheat the polyurethane elastomer and EPDM rubber at 55-60°C for 30-45 minutes; Step 3, mixing: adding the pretreated nanomaterials and the preheated polyurethane elastomer and EPDM rubber into a high-speed mixer, mixing at a speed of 800-1000 r / min for 15-20 min, adding random copolymer polypropylene, low-density polyethylene, ethylene-octene polymer, bronze powder, antioxidant, oleic acid amide and silicone masterbatch into the mixture, and continuing to mix at a speed of 1000-1200 r / min for 25-35 min; Step 4: Melt extrusion: Add the mixed materials into a twin-screw extruder, set the extrusion temperature to 200-215°C, and the screw speed to 250-300r / min. During the extrusion process, remove volatile impurities through a vacuum degassing system; Step 5: Cooling and pelletizing: The blended melt is rapidly cooled by water cooling and then pelletized; Step 6, injection molding: the pelletized particles are molded by an injection molding machine, the injection molding temperature is controlled between 210°C and 215°C, and the pressure is controlled between 65MPa and 70MPa to obtain a new polypropylene composite material; Step seven, post-processing: annealing the new polypropylene composite material after injection molding to finally obtain a modified polypropylene material.

[0013] Preferably, the conditions of the vacuum degassing system in step 4 are: the vacuum degree of the degassing system is maintained between 0.5-1.0 Torr, and the degassing time is 105% to 110% times the extrusion time.

[0014] Preferably, the cooling and pelletizing conditions in step 5 are: using deionized water as the cooling medium, the temperature is controlled between 5-15° C., the pelletizing speed is 200-300 r / min, and the particle size after pelletizing is controlled between 3-5 mm.

[0015] Preferably, in the post-treatment in step seven: the novel polypropylene composite material is annealed at 95-100° C. for 4-6 hours, and then naturally cooled at room temperature after annealing to obtain a modified polypropylene material.

[0016] Compared with the prior art, the present invention provides a highly wear-resistant modified polypropylene material and a preparation process, which has the following beneficial effects: 1. The present invention uses random copolymerized polypropylene instead of conventional polypropylene, adds low-density polyethylene in a formula ratio as a base resin, uses bronze powder and nano-grade materials as filling materials and additives, and combines a set preparation process. The toughness and low-temperature performance of the prepared material are greatly improved, and the final finished material has increased cold resistance and low-temperature impact. Among them, the addition of bronze powder can enhance the wear resistance and mechanical properties of the material, making the material more durable in practical applications, and adding appropriate amounts of nano-grade zinc oxide and nano-grade silicon carbide to the original compatible raw material-ethylene-octene polymer can further increase the original compatibility of the material. The highly wear-resistant modified polypropylene material finally prepared shows excellent performance in cold resistance, low-temperature impact, wear resistance and material compatibility, and can be suitable for various application scenarios requiring high wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A flow chart was prepared for the present invention. DETAILED DESCRIPTION

[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] See also Figure 1 A highly wear-resistant modified polypropylene material, the material is composed of a base resin, a toughening agent, an elastomer, a wear-resistant filler, a reinforcing agent, a compatibilizer, a surface lubricant and an additive. The raw materials and their weight portions include: 40-50 parts of random copolymer polypropylene (L5E89); 10-14 parts of low-density polyethylene (LDPE); 6-10 parts of ethylene propylene diene rubber (EPDM); 7-9 parts of nano-scale silicon carbide (SiC); 10-13 parts of ethylene-octene polymer (POE); 5-8 parts of polyurethane elastomer (PU); 1.3-1.8 parts of bronze powder; 4-5 parts of nano-scale zinc oxide (ZnO); 2-4 parts of antioxidant (1010); 0.8-1.1 parts of oleic acid amide; and 1.5-3 parts of silicone masterbatch.

[0020] The following table 1 shows the raw materials and their corresponding functions: Table 1 Raw material name Weight range Features and functions Random copolymer polypropylene (L5E89) 40-50 servings Base resin, which provides the material's matrix strength and rigidity Low-density polyethylene (LDPE) 10-14 servings Toughening agent, improves the toughness and impact strength of materials EPDM 6-10 servings Elastomers increase the flexibility and wear resistance of the material Nano-scale Silicon Carbide (SiC) 7-9 servings Wear-resistant filler, significantly improving the wear resistance of the material Ethylene-octene polymer (POE) 10-13 servings Compatibilizer, improves the compatibility between different components and enhances the comprehensive performance of materials Polyurethane elastomer (PU) 5-8 servings Reinforcement agent to further improve the wear resistance and impact resistance of the material Bronze powder 1.3-1.8 servings Surface lubricant, reducing friction coefficient and improving surface smoothness Nano-ZnO 4-5 servings Additives to provide antimicrobial and thermal stability Antioxidant (1010) 2-4 servings Additives to prevent oxidation and degradation of materials and extend service life Oleamide 0.8-1.1 parts Additives, used as lubricants, reducing internal friction Silicone Masterbatch 1.5-3 servings Additives to improve material processing fluidity and surface properties Specifically, the base resin is composed of random copolymer polypropylene and low-density polyethylene, the toughening agent is composed of EPDM rubber and ethylene-octene polymer, the elastomer is composed of polyurethane elastomer, the wear-resistant filler is composed of nano-grade silicon carbide and bronze powder, the reinforcing agent is composed of nano-grade zinc oxide, the compatibilizer is composed of silicone masterbatch, the surface lubricant is composed of oleic acid amide, and the additive is composed of antioxidant.

[0021] Specifically, the preparation process of random copolymer polypropylene: S1.1. Prepare raw materials: prepare ethylene and propylene in a molar ratio of 0.01-0.04 and add them into the reactor; S1.2, control the reactor conditions: control the reactor temperature between 60-80°C, and the reactor pressure between 2-4MPa; S1.3, polymerization reaction: adding 2% metallocene catalyst based on the total mass of ethylene and propylene into the reactor, controlling the reaction time to be between 15 and 30 minutes, and obtaining a reactant; S1.4. Separation and purification: After the polymerization reaction is completed, the reactants are separated and purified to remove unreacted monomers and other impurities, and finally random copolymer polypropylene is obtained.

[0022] Specifically, the microhardness of nano-scale silicon carbide is 2840-3320kg / mm², which is between corundum and diamond, and its mechanical strength is higher than corundum. The particle size of nano-scale zinc oxide is 30-100nm, the average particle size is 50nm, and the specific surface area is greater than 4m² / g.

[0023] Specifically, a preparation process of a highly wear-resistant modified polypropylene material is prepared according to the raw materials and weight portions of the above-mentioned highly wear-resistant modified polypropylene material, and the preparation process is as follows: Step 1, raw material preparation: prepare the formula weight parts of random copolymer polypropylene, low-density polyethylene, ethylene propylene diene monomer rubber, nano-silicon carbide, ethylene-octene polymer, polyurethane elastomer, bronze powder, nano-zinc oxide, antioxidant, oleic acid amide and silicone masterbatch. Before weighing, conduct a quality inspection on each batch of raw materials to check whether their appearance, color, smell, etc. are normal, confirm that there are no impurities, no lumps, and no deterioration, ensure the purity and consistency of the raw materials, avoid affecting the performance of the final product due to raw material quality problems, and ensure that the raw materials are weighed accurately during the final weighing; Step 2, pretreatment: subject nano-sized silicon carbide and nano-sized zinc oxide to ultrasonic dispersion treatment for 20-30 minutes to ensure their uniform dispersion. The cavitation effect and mechanical vibration of ultrasound can effectively break up the agglomeration of nano-particles, making them uniformly dispersed in the solution to form a stable nano-dispersion liquid, which provides a good dispersion basis for subsequent mixing with other materials. Preheat the polyurethane elastomer and EPDM rubber at 55-60°C for 30-45 minutes to improve their mixing uniformity. During the preheating process, the molecular chain segments of rubber and elastomer increase in activity and plasticity, which helps to better integrate with other materials in the subsequent mixing process, improve mixing uniformity, and also help to reduce energy consumption during the mixing process; Step 3, mixing: adding the pretreated nanomaterials and preheated polyurethane elastomers and EPDM rubber to a high-speed mixer, and mixing at a speed of 800-1000r / min for 15-20min. This stage is preliminary mixing, and the main purpose is to make the nanomaterials initially combine with the rubber and elastomer to form a relatively uniform dispersed phase, so as to prepare for the subsequent comprehensive mixing. Add random copolymer polypropylene, low-density polyethylene, ethylene-octene polymer, bronze powder, antioxidant, oleic acid amide and silicone masterbatch to the above mixture, and continue to mix at a speed of 1000-1200r / min for 25-35min. At this stage, various materials are fully mixed to form a uniform composite material mixture. During the mixing process, the shear force and friction force of the mixer further promote the entanglement and fusion of the molecular segments between the materials, thereby improving the compatibility and uniformity of the materials. Step 4: Melt extrusion: Add the mixed materials into a twin-screw extruder, set the extrusion temperature to 200-215°C, and the screw speed to 250-300r / min. During the extrusion process, remove volatile impurities through a vacuum degassing system. The screw design and shearing force of the twin-screw extruder help to further improve the mixing uniformity and dispersion of the materials, and the degassing system can effectively remove volatile impurities and gases in the melt, such as moisture and low molecular weight volatiles, to prevent the generation of bubbles and hole defects in the subsequent molding process, thereby improving the density and mechanical properties of the material; Step 5, cooling and pelletizing: The blended melt is quickly cooled by water cooling. The water cooling method has a fast cooling speed and can effectively control the crystal morphology and size of the material, which is beneficial to improve the toughness and strength of the material, and then pelletizing is performed; during the pelletizing process, the pelletizing speed and particle size are controlled to ensure that the particles are uniform and consistent, which is convenient for subsequent injection molding; Step 6, injection molding: Dry the pelletized particles to remove moisture from the surface of the particles to prevent water vapor from being generated during the injection molding process, which affects the molding quality and material properties. Then, the dried and pelletized particles are molded by an injection molding machine. The injection molding temperature is controlled between 210°C and 215°C, and the pressure is controlled between 65MPa and 70MPa. During the injection molding process, the injection speed, holding time and cooling time parameters are controlled to ensure the uniformity and mechanical properties of the products, avoid defects such as warping and shrinkage, ensure the uniformity and mechanical properties of the products, and obtain a new type of high-performance polypropylene composite material; Step 7. Post-processing: Anneal the new polypropylene composite material after injection molding. During the annealing process, the molecular segments inside the material are rearranged and relaxed, which can effectively eliminate internal stress and improve the toughness and impact resistance of the material. It also helps to stabilize the size and shape of the material to prevent deformation during subsequent use, thereby eliminating internal stress, improving the toughness and impact resistance of the material, and finally obtaining a modified polypropylene material.

[0024] The advantages are: by using random copolymer polypropylene instead of conventional polypropylene, adding a formula ratio of low-density polyethylene as the base resin, using bronze powder and nano-scale materials as filling materials and additives, and combining the above-mentioned preparation process, the toughness and low-temperature performance of the prepared material are greatly improved, and the final finished material has increased cold resistance and low-temperature impact. Among them, the addition of bronze powder can enhance the wear resistance and mechanical properties of the material, making the material more durable in practical applications, and adding appropriate amounts of nano-scale zinc oxide and nano-scale silicon carbide to the original compatible raw material-ethylene-octene polymer can further increase the original compatibility of the material. The finally made high wear-resistant modified polypropylene material shows excellent performance in cold resistance, low-temperature impact, wear resistance and material compatibility, and can be suitable for various application scenarios requiring high wear resistance.

[0025] Specifically, the conditions of the vacuum degassing system in step 4 are: the vacuum degree of the degassing system is maintained between 0.5-1.0 Torr, and the degassing time is 105% to 110% times the extrusion time.

[0026] Specifically, the cooling and pelletizing conditions in step five are: using deionized water as the cooling medium, the temperature is controlled between 5-15° C., the pelletizing speed is 200-300 r / min, and the particle size after pelletizing is controlled between 3-5 mm.

[0027] Specifically, in step seven, the post-treatment is as follows: the new polypropylene composite material is annealed at 95-100° C. for 4-6 hours, and then naturally cooled at room temperature after annealing to eliminate internal stress, thereby obtaining a modified polypropylene material. Example 1

[0028] Specifically, the raw materials and their weight parts include: 45 parts of random copolymer polypropylene; 13 parts of low-density polyethylene; 9 parts of EPDM rubber; 9 parts of nano-silicon carbide; 11 parts of ethylene-octene polymer; 6 parts of polyurethane elastomer; 1.35 parts of bronze powder; 4.2 parts of nano-zinc oxide; 2.2 parts of antioxidant; 0.98 parts of oleic acid amide; and 1.8 parts of silicone masterbatch. Comparative Example 1

[0029] Specifically, the raw materials and their weight parts include: 45 parts of polypropylene; 13 parts of low-density polyethylene; 9 parts of EPDM rubber; 9 parts of nano-silicon carbide; 11 parts of ethylene-octene polymer; 6 parts of polyurethane elastomer; 4.2 parts of nano-zinc oxide; 2.2 parts of antioxidant; 0.98 parts of oleic acid amide; and 1.8 parts of silicone masterbatch. Example 2

[0030] Specifically, the raw materials and their weight parts include: 50 parts of random copolymer polypropylene; 11 parts of low-density polyethylene; 7 parts of EPDM rubber; 7 parts of nano-silicon carbide; 13 parts of ethylene-octene polymer; 5 parts of polyurethane elastomer; 1.7 parts of bronze powder; 4.4 parts of nano-zinc oxide; 2.6 parts of antioxidant; 0.91 parts of oleic acid amide; and 2.4 parts of silicone masterbatch. Comparative Example 2

[0031] Specifically, the raw materials and their weight parts include: 55 parts of random copolymer polypropylene; 11 parts of low-density polyethylene; 7 parts of EPDM rubber; 13 parts of ethylene-octene polymer; 5 parts of polyurethane elastomer; 1.7 parts of bronze powder; 8.4 parts of nano-grade zinc oxide; 2.6 parts of antioxidant; 0.91 parts of oleic acid amide; and 2.4 parts of silicone masterbatch.

[0032] The finished materials made by Example 1 and Comparative Example 1 are compared, and the finished materials made by Example 2 and Comparative Example 2 are compared. The performance test table obtained is as follows Table 2: Performance Indicators Example 1 Comparative Example 1 Example 2 Comparative Example 2 Cold resistance (℃) -30 -25 -35 -30 Low temperature impact resistance (J / m) 120 80 130 90 Abrasion resistance (g / 1000m) 0.5 0.8 0.4 0.7 Material compatibility (%) 100% 88% 95% 75%

[0033] Comparison of Example 1 and Comparative Example 1 Raw material comparison: Random copolymer polypropylene and polypropylene: Random copolymer polypropylene is used in Example 1, while conventional polypropylene is used in Comparative Example 1. Random copolymer polypropylene has better toughness and low-temperature performance, which will make the finished material of Example 1 perform better in cold resistance and low-temperature impact resistance; Addition of bronze powder: 1.35 parts of bronze powder was added to Example 1, while no bronze powder was added to Comparative Example 1. The wear resistance and mechanical properties of the material in Example 1 were better than those in Comparative Example 1. Therefore, the addition of bronze powder can improve the wear resistance and mechanical properties of the finished material. Cold resistance: The cold resistance of Example 1 is -30°C, which is better than -25°C of Comparative Example 1, indicating that the use of random copolymer polypropylene can improve the cold resistance of the material; Low temperature impact resistance: The low temperature impact resistance of Example 1 is 120 J / m, which is much higher than 80 J / m of Comparative Example 1. This further proves that the combination and weight ratio of random copolymerized polypropylene and bronze powder in the formula of the present invention can improve the toughness of the material; Wear resistance: The wear resistance of Example 1 is 0.5 g / 1000m, which is lower than 0.8 g / 1000m of Comparative Example 1, indicating that the addition of bronze powder in Example 1 can effectively improve the wear resistance of the material; Material compatibility: The material compatibility of Example 1 is 100%, which is better than 88% of Comparative Example 1. This shows that the random copolymer polypropylene and other components under this combination of raw materials by weight have good compatibility, which helps to improve the overall performance of the material.

[0034] Comparison of Example 2 and Comparative Example 2 Raw material comparison: The amount of random copolymer polypropylene used: the amount of random copolymer polypropylene used in Example 2 is 50 parts, while that in Comparative Example 2 is 55 parts. Although the amount used in Comparative Example 2 is higher, its performance is not as good as that in Example 2; The amount of nano-zinc oxide used: the amount of nano-zinc oxide used in Example 2 is 4.4 parts, while that used in Comparative Example 2 is 8.4 parts. It can be seen that excessive nano-zinc oxide will reduce the compatibility and other properties of the material. Comparative Example 2 lacks nano-silicon carbide. Cold resistance: The cold resistance of Example 2 is -35°C, which is better than -30°C of Comparative Example 2, which shows that the increase of nano-grade zinc oxide in the formula of Example 2 can improve the cold resistance of the finished material; Low temperature impact resistance: The low temperature impact resistance of Example 2 is 130 J / m, which is higher than 90 J / m of Comparative Example 2. This shows that the random copolymerized polypropylene of Example 2 is combined with the nano-scale material, so that the finished material has high toughness and strong impact resistance; Wear resistance: The wear resistance of Example 2 is 0.4 g / 1000m, which is lower than 0.7 g / 1000m of Comparative Example 2, indicating that the material of Example 2 has better wear resistance; Material compatibility: The material compatibility of Example 2 is 95%, which is better than 75% of Comparative Example 2. Since the dosage of nano-zinc oxide in Example 2 is more appropriate, the negative impact of excessive nano-materials can be effectively avoided. At the same time, the ratio of bronze powder, nano-zinc oxide and other components at this dosage is also more conducive to improving compatibility.

[0035] In summary, the material formulations of Example 1 and Example 2 are superior to the corresponding control examples in terms of cold resistance, low-temperature impact resistance and wear resistance, and the material compatibility is also better, which shows that the use of random copolymer polypropylene and the appropriate ratio of nano-silicon carbide and nano-zinc oxide have a significant positive effect on improving material properties.

[0036] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A highly wear-resistant modified polypropylene material, characterized in that: The material consists of a base resin, a toughening agent, an elastomer, a wear-resistant filler, a reinforcing agent, a compatibilizer, a surface lubricant and an additive. The raw materials and their weight proportions include: 40-50 parts of random copolymer polypropylene; 10-14 parts of low-density polyethylene; 6-10 parts of EPDM rubber; 7-9 parts of nano-grade silicon carbide; 10-13 parts of ethylene-octene polymer; 5-8 parts of polyurethane elastomer; 1.3-1.8 parts of bronze powder; 4-5 parts of nano-grade zinc oxide; 2-4 parts of antioxidant; 0.8-1.1 parts of oleic acid amide; and 1.5-3 parts of silicone masterbatch.

2. A highly wear-resistant modified polypropylene material according to claim 1, characterized in that: The base resin is composed of random copolymer polypropylene and low-density polyethylene, the toughening agent is composed of EPDM rubber and ethylene-octene polymer, the elastomer is composed of polyurethane elastomer, the wear-resistant filler is composed of nano-scale silicon carbide and bronze powder, the reinforcing agent is composed of nano-scale zinc oxide, the compatibilizer is composed of silicone masterbatch, the surface lubricant is composed of oleic acid amide, and the auxiliary agent is composed of an antioxidant.

3. A highly wear-resistant modified polypropylene material according to claim 1, characterized in that: The raw materials and their weight parts include: 45 parts of random copolymer polypropylene; 13 parts of low-density polyethylene; 9 parts of EPDM rubber; 9 parts of nano-grade silicon carbide; 11 parts of ethylene-octene polymer; 6 parts of polyurethane elastomer; 1.35 parts of bronze powder; 4.2 parts of nano-grade zinc oxide; 2.2 parts of antioxidant; 0.98 parts of oleic acid amide; and 1.8 parts of silicone masterbatch.

4. A highly wear-resistant modified polypropylene material according to claim 1, characterized in that: The raw materials and their weight parts include: 50 parts of random copolymer polypropylene; 11 parts of low-density polyethylene; 7 parts of ethylene propylene diene rubber; 7 parts of nano-grade silicon carbide; 13 parts of ethylene-octene polymer; 5 parts of polyurethane elastomer; 1.7 parts of bronze powder; 4.4 parts of nano-grade zinc oxide; 2.6 parts of antioxidant; 0.91 parts of oleic acid amide; and 2.4 parts of silicone masterbatch.

5. The highly wear-resistant modified polypropylene material according to claim 1, characterized in that: The preparation process of the random copolymer polypropylene: S1.

1. Prepare raw materials: prepare ethylene and propylene in a molar ratio of 0.01-0.04 and add them into the reactor; S1.2, control the reactor conditions: control the reactor temperature between 60-80°C, and the reactor pressure between 2-4 MPa; S1.3, polymerization reaction: adding 2% metallocene catalyst based on the total mass of ethylene and propylene into the reactor, controlling the reaction time to be between 15 and 30 minutes, and obtaining a reactant; S1.

4. Separation and purification: After the polymerization reaction is completed, the reactants are separated and purified to remove unreacted monomers and other impurities, and finally random copolymer polypropylene is obtained.

6. A highly wear-resistant modified polypropylene material according to claim 1, characterized in that: The microhardness of the nano-scale silicon carbide is 2840-3320 kg / mm², which is between corundum and diamond, and the mechanical strength is higher than that of corundum. The particle size of the nano-scale zinc oxide is 30-100 nm, the average particle size is 50 nm, and the specific surface area is greater than 4 m² / g.

7. A preparation process of a highly wear-resistant modified polypropylene material, characterized in that: The raw materials and weight portions of the highly wear-resistant modified polypropylene material according to claim 1 are prepared, and the preparation process is as follows: Step 1, raw material preparation: prepare random copolymer polypropylene, low-density polyethylene, EPDM rubber, nano-silicon carbide, ethylene-octene polymer, polyurethane elastomer, bronze powder, nano-zinc oxide, antioxidant, oleic acid amide and silicone masterbatch in parts by weight of the formula; Step 2, pretreatment: subject nano-sized silicon carbide and nano-sized zinc oxide to ultrasonic dispersion treatment for 20-30 minutes, and preheat the polyurethane elastomer and EPDM rubber at 55-60°C for 30-45 minutes; Step 3, mixing: adding the pretreated nanomaterials and the preheated polyurethane elastomer and EPDM rubber into a high-speed mixer, mixing at a speed of 800-1000 r / min for 15-20 min, adding random copolymer polypropylene, low-density polyethylene, ethylene-octene polymer, bronze powder, antioxidant, oleic acid amide and silicone masterbatch into the mixture, and continuing to mix at a speed of 1000-1200 r / min for 25-35 min; Step 4: Melt extrusion: Add the mixed materials into a twin-screw extruder, set the extrusion temperature to 200-215°C, and the screw speed to 250-300r / min. During the extrusion process, remove volatile impurities through a vacuum degassing system; Step 5: Cooling and pelletizing: The blended melt is rapidly cooled by water cooling and then pelletized; Step 6, injection molding: the pelletized particles are molded by an injection molding machine, the injection molding temperature is controlled between 210°C and 215°C, and the pressure is controlled between 65MPa and 70MPa to obtain a new polypropylene composite material; Step seven, post-processing: annealing the new polypropylene composite material after injection molding to finally obtain a modified polypropylene material.

8. The process for preparing a highly wear-resistant modified polypropylene material according to claim 7, characterized in that: The conditions of the vacuum degassing system in step 4 are as follows: the vacuum degree of the degassing system is maintained between 0.5-1.0 Torr, and the degassing time is 105% to 110% of the extrusion time.

9. The process for preparing a highly wear-resistant modified polypropylene material according to claim 7, characterized in that: The cooling and pelletizing conditions in step 5 are as follows: deionized water is used as the cooling medium, the temperature is controlled between 5-15° C., the pelletizing speed is 200-300 r / min, and the particle size after pelletizing is controlled between 3-5 mm.

10. The process for preparing a highly wear-resistant modified polypropylene material according to claim 7, characterized in that: In the post-treatment of step seven, the novel polypropylene composite material is annealed at 95-100° C. for 4-6 hours, and then naturally cooled at room temperature to obtain a modified polypropylene material.

Citation Information

Patent Citations

  • Highly wear-resistant low-noise glass fiber reinforced nylon composite material composition and preparation method thereof

    CN103788629A

  • Scratch-resistant impact-resistant polypropylene material and preparation method thereof

    CN110655710A